Implementation of Individual Learning for Children with Special Needs - Hastuti, Isnaini Budi; Musslifah, Annies Rachmawati (Early Childhood Research Journal (ECRJ), 2023)
The rise of schools with the concept of inclusion needs to be balanced with the right curriculum, especially with regard to the learning process. The purpose of this study is to explain the implementation of learning for children with special needs at the PAUD level in accordance with the regulations of the Ministry of Education and Culture. The object of this research is Saymara Inclusion Early childhood education programs. The reason for choosing this education unit was that Saymara Inclusion PAUD is an Inclusive PAUD level education in Kartasura and received an A rating in Accreditation. Research uses an empirical or field approach. The results of the study show that learning for children with special needs is based on the Individual Learning Program, where children with special needs are given services according to their needs, and focus on the abilities and weaknesses of students.